Case reportIndividual applicator for brachytherapy for various sites of superficial malignant lesions - Kowalik, Łukasz; Łyczek, Jarosław; Sawicki, Marcin; Kazalski, Damian (Journal of Contemporary Brachytherapy, 2013)
The aim of this paper is to discuss brachytherapy treatment and individual applicators suitable for unfavorably localized superficial malignant lesions. Techniques for manufacturing an individual applicator and clinical examples of its use for various locations of cancer are presented. This techniques are based on individual size and shape of the tumour. CT-planning make the technique adequate for individual patient history and type of tumour. Featured techniques seems to be very useful and easy to performed.